Media Secret Alphabet Berbasis Loose Part untuk Meningkatkan Kemampuan Keaksaraan Awal Anak Usia 4-5 Tahun - Syaripatunisa, Virda; Rahman, Taopik; Azhar Yamin, Alfian (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
This study aims to describe the planning, implementation and improvement carried out by teachers in early literacy skills in children aged 4-5 years through the use of loose part-based secret alphabet media. The research method used is Classroom Action Research (CAR) which is carried out collaboratively with teachers at Kober Al-Urwatul Wutsqa. The subjects of the study included 12 children in group A, consisting of 5 boys and 7 girls. Data collection techniques in this study were through observation and documentation techniques, then analyzed using narrative and graphic analysis. The results of the study indicate that the use of loose part-based secret alphabet media can improve the early literacy skills of children aged 4-5 years in recognizing letters A-Z. Children's early literacy skills can be seen from each stage of learning which shows that children can recognize sounds and shapes/symbols of letters, children can distinguish sounds and shapes of similar letters, and children can imitate letter shapes. This success cannot be separated from careful planning, optimal implementation, and the use of loose part-based secret alphabet media which is able to attract interest and increase children's active participation in learning activities. Based on the results of this study, the use of creative, innovative learning media, such as loose part-based secret alphabet media, is very effective in improving the early literacy skills of children aged 4-5 years